Studi Evaluasi Efektivitas Sistem Manajemen Kepegawaian (Simpeg) Bagi Guru Berstatus Pegawai Negeri Sipil (Pns) Di Kecamatan Abiansemal Kabupaten Badung. - Putu Yurika Pradnya Sasmitha; Kadek Rihendra Dantes; Basilius Redan Werang (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to 1) determine the effectiveness of the Personnel Management Information System (Simpeg) for Teachers with Civil Servant Status (PNS) in Abiansemal District, Badung Regency and 2) find out what factors influence the effectiveness of the Personnel Management Information System (Simpeg) for Teachers Has the status of a Civil Servant (PNS) in Abiansemal District, Badung Regency. This research is an evaluation research with CIPP design (Context, Input, Process, Product). The population used in this study were teachers with civil servant status (PNS) in Abiansemal District, Badung Regency, totaling 537 teachers ranging from elementary, junior high and DPK teachers. While the sample used in this study used a random sampling technique, the minimum number of samples that must be used in this study was 226. The data collection method used in this study was a questionnaire and documentation method. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of the raw score data transformed into Z-scores then into T-Scores then verified into the Glickman Quadrant. Based on the research that has been done, the results show that: 1) The effectiveness of the Personnel Management System (SIMPEG) for Teachers with Civil Servant Status (PNS) in Abiansemal District, Badung Regency, in terms of context, obtained effective results (+), 2) Effectiveness of the Personnel Management System (SIMPEG) For Teachers with Civil Servant Status (PNS) in Abiansemal District, Badung Regency, in terms of input, effective results are obtained (+), 3) Effectiveness of the Personnel Management System (SIMPEG) for Teachers with Civil Servant Status (PNS) in Abiansemal District, Regency Badung in terms of process obtained effective results (+), 4) Effectiveness of the Personnel Management System (SIMPEG) for Teachers with Civil Servant Status (PNS) in Abiansemal District, Badung Regency in terms of product obtained effective results (+), and 5) Results joint evaluation of the Effectiveness of the Personnel Management System (SIMPEG) for Teachers with Civil Servant Status (PN S) in Abiansemal District, Badung Regency, seen from the context, input, process and product aspects, effective results were obtained (+ + + +).